Culture Shock Pada Mahasiswa Asal Papua di Universitas Malikussaleh - Nurjannah Nasution; Safuwan Safuwan (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
This study aims to understand how culture shock occurs in Papuan students in Malikussaleh University Aceh. This study was designed with phenomenological type by qualitative approach. Subject of this study was selected by purposive sampling technique, there was six students from Papua in semester one and three chosen to be subject. Data collection method used observations and indepth interview. The data analysis technique used is Creswell Analysis technique by analyzing the theme and then interpreting result. The result show that dimension of culture shock was experienced by all of participants, Then in terms of procces culture shock, four partiscipants has been experience and left four phase of culture shock, and two more are still in the third phase or recovery phase. Culture shock has occurs in Papuan studets is influenced by factors such as individual difference, cross cultures experience, differences in quality, quantity and durations of culture shock.